Foreign currency and interest rate hedging and firm value : Swedish listed firms 2009–2014 - Hilanne, Mira (My University, 2021)
The effect of hedging with financial derivatives on firm market value is examined with more than 200 non-financial firms listed in NASDAQ Stockholm during 2009–2014. Out of the 1285 firm year observations, 695 observations are classified as firms that disclose a derivative position in their annual report during the respective sample year. The focus is on foreign currency (FC) and interest rate (IR) derivatives and how hedging impacts on firm value and corporate risk management decisions. The dependent variable, Tobin’s Q, is a proxy for firm value, which is a common practice in previous studies. The findings provide empirical evidence that hedging declines firm value. Non-hedgers are rewarded with a positive Tobin’s Q of 0.238 in mean values over hedgers on average. The findings are opposite of the expected outcome that hedgers are rewarded with a higher premium value. Furthermore, the univariate results indicate similar results of negative values in all type of hedgers, foreign currency and interest rate hedgers. In addition, the findings of comparative analyses between FC and IR hedging indicate more ambiguous results depending on the models. The potential issue of variables is the existence of endogeneity, which is controlled with firm-specific control variables such as size, leverage, profitability, and time effects in the multivariate analyses. Endogeneity refers to the possibility of firm market value being derived from other factors than hedging. Therefore, positive hedging premium may not be an outcome of hedging. The multivariate models are examined with unbalanced panel data of Pooled model, Fixed Effects and Random Effects models. The findings of multivariate regressions are inconsistent in comparison to univariate analyses. On average, hedgers have negative Tobin’s Qs ranging between -6.10% and -15.30% for various hedgers. However, not all the results are statistically significant, and some models indicate a positive result for hedgers despite not being statistically significant. The models are also estimated for industry-specific categories where each industry is studied separately regarding Tobin’s Q. The results are more ambiguous when individual industries are studied separately, and industry-specific differences exist. In fact, in some industries hedgers benefit from hedging premium over non-hedgers. Nonetheless, most of the results are not statistically significant. Furthermore, to check the robustness of findings, a selection bias and omitted variables are estimated with Heckman’s treatment effects model. The results imply that coefficients indicate similar values as with other multivariate models.

Yrityksien riskienhallinta pitää sisällään johdannaisinstrumenteilla suojautumisen erilaisia valuutta- ja korkoriskejä vastaan. Tutkimuksen tavoitteena on selvittää miten johdannaisinstrumenttien käyttö suojautumismekanismina vaikuttaa yrityksien markkina-arvoon Tukholman pörssissä noteeratuissa yrityksissä vuosina 2009–2014. Tutkimuksen otanta sisältää 1285 yrityshavaintoa, joista 695 havaintoa luokitellaan suojatuiksi, mikä tarkoittaa, että yritys ilmoittaa johdannaisposition vuosikertomuksessaan kyseisen otosvuoden aikana. Yrityksiä on yli 200 per otosvuosi. Keskeisenä riippuvana muuttujana hyödynnetään Tobinin Q:ta, joka kuvaa yrityksen markkina-arvoa. Tutkimuksen hypoteesi perustuu aikaisempiin tutkimustuloksiin, joissa johdannaisia käyttävät yritykset omaavat korkeamman markkina-arvon eli Tobinin Q:n. Vastoin oletuksia, tulokset osoittavat, että suojautuvien yritysten markkina-arvo on negatiivinen. Ei-suojautuvat yritykset palkitaan keskimäärin 0,238 suojautumispreemiolla keskiarvotuloksissa. Lisäksi regressioanalyysien tulokset ovat hyvin samankaltaisia eli ne indikoivat negatiivisen kertoimen suojautuville yrityksille. Tutkimus tarkastelee myös valuutta- ja korkojohdannaisten välisiä eroja suojautumispreemiossa ja tutkimustulokset vaihtelevat eri mallien välillä. Tutkimuksen potentiaalinen ongelma on endogeenisuuden olemassaolo, jota kontrolloidaan yrityskohtaisilla kontrollimuuttujilla, kuten koko, vipuvaikutus, kannattavuus ja aikavaikutus monimuuttujaregressioissa. Endogeenisuudella tarkoitetaan ongelmaa, jossa yrityksen markkina-arvo perustuu muihin tekijöihin kuin johdannaisilla suojautumiseen. Näin ollen positiivinen suojautumispreemio ei välttämättä ole johdannaisten käytön tulos. Monimuuttuja-analyyseissa tarkastellaan erilaisia malleja hyödyntäen paneelidataa. Monimuuttujaregressioiden havainnot ovat epäjohdonmukaisia verrattuna yhden muuttujan regressioanalyyseihin. Useimmissa malleissa tuloksena on negatiivinen kerroin, mutta kaikki tulokset eivät kuitenkaan ole tilastollisesti merkittäviä. Keskimäärin suojautuvien yritysten kertoimet ovat negatiivisia ja vaihtelevat -6,10 % ja -15,30 % välillä. Tutkimus rajataan myös yksittäisiin toimialoihin, minkä tarkoituksena on selvittää miten Tobinin Q:n arvot muuttuvat eri toimialoilla. Tutkimustulokset osoittavat, että toimialakohtaisia eroja Tobinin Q:n välillä on, ja osa aloista palkitaan positiivisilla suojautumispreemioilla. Suurin osa tuloksista eivät ole kuitenkaan tilastollisesti merkittäviä. Lisäksi tutkimus tarkastelee valintapoikkeamia Heckman-mallin avulla, joka vahvistaa aikaisemmat tulokset.
Keywords: Firm value, hedging, corporate risk management, foreign currency derivatives, interest rate derivatives, Tobin’s Q